In situ observation of rolling contact fatigue cracks by laminography using ultrabright synchrotron radiation - Y. Nakai; D. Shiozawa,; S. Kikuchi; K. Sato; T. Obama; T. Makino; Y. Neishi (Fracture and Structural Integrity)
In rolling contact fatigue (RCF), cracks usually initiate from inclusions beneath the surface and propagate to the contact surface. In the present study, synchrotron radiation computed laminography (SRCL) imaging was performed to observe flaking defects during the RCF of a high-strength steel. Specially fabricated inclusion-rich steel plate specimens were employed in the experiments. For the in situ observation of crack propagation, a compact RCF testing machine was developed, and a 4D analysis scheme was applied to the data obtained by SRCL. RCF tests were carried out near the measurement hatch of the beam line used SRCL to enable the successive observation of crack initiation and growth behaviors. Specimens before and after the occurrence of flaking were observed by SRCL, and flaking defects and cracks under the surface were successfully detected. As a result, details of the crack initiation and flaking process in RCF could be discussed. Shear-type horizontal cracks were found to initiate after the initiation and propagation of tensile-type vertical cracks along inclusions, where the face of the vertical cracks was perpendicular to the rolling direction and rolling surface. Therefore, the formation of vertical cracks is considered to affect shear-type crack formation and flaking, where the shape and length of inclusions also affect the initiation and propagation of vertical cracks.